Thomas' Calculus 13th Edition

Published by Pearson
ISBN 10: 0-32187-896-5
ISBN 13: 978-0-32187-896-0

Chapter 3: Derivatives - Section 3.3 Differentiation Rules - Exercises 3.3 - Page 125: 7


First Derivative: $w'=\frac{-6}{z^{3}}+\frac{1}{z^{2}}$ Second Derivative: $w''=\frac{18}{z^{4}}-\frac{2}{z^{3}}$

Work Step by Step

Using the power rule: First Derivative: $w=3z^{-2}-\frac{1}{z}$ $w'=(-2)(3)z^{-2-1}-(-1)z^{-1-1}$ $w'=-6z^{-3}+z^{-2}$ $w'=\frac{-6}{z^{3}}+\frac{1}{z^{2}}$ Second Derivative: $w'=-6z^{-3}+z^{-2}$ $w''=(-3)(-6)z^{-3-1}+(-2)z^{-2-1}$ $w''=18z^{-4}-2z^{-3}$ $w''=\frac{18}{z^{4}}-\frac{2}{z^{3}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.